Sistem Informasi Kehadiran Karyawan Berbasis Web Dengan Metodologi Agile Software Development di Balai Latihan Kerja Kabupaten Balangan - Abdillah, Muhammad Lutfi; Pantjarani, Ari; Hamid, Abdul (Indonesian Journal of Information Technology and Computing (IMAGING), 2025)
The Employee Attendance Information System (SIKK) has become an integral part of human resource management in modern organizations. In an effort to improve efficiency and flexibility, the Agile Software Development approach has been applied in the development of a web-based SIKK. The development of the web-based Employee Attendance Information System (SIKK) at the Training Center (BLK) aims to address issues of efficiency and accuracy in attendance monitoring, which were previously managed manually. The objective of this research is to develop and implement a web-based employee attendance information system using the Agile Software Development methodology, focused on the BLK institution. This study aims to enhance the effectiveness of employee attendance monitoring, operational efficiency, and responsiveness to changes in user needs. By using the Agile Software Development methodology, the system is developed iteratively and collaboratively between the development team and end-users, allowing for quick responses to feedback and changing requirements. This research also aims to ensure the system's flexibility in accommodating user feedback and rapid changes in the work environment, as well as evaluate its impact on time efficiency, attendance data accuracy, performance management, and payroll calculation. The results indicate that the developed SIKK has improved attendance management effectiveness, reduced data processing time, and enhanced payroll calculation accuracy as well as performance management, thereby positively impacting operational efficiency at BLK.